Grapevine Fanleaf Virus RNA1-Encoded Proteins 1A and 1BHel Suppress RNA Silencing - Choi, Jiyeong; Pakbaz, Samira; Yepes, Luz Marcela; Cieniewicz, Elizabeth Jeannette; Schmitt-Keichinger, Corinne; Labarile, Rossella; Minutillo, Serena Anna; Heck, Michelle; Hua, Jian; Fuchs, Marc (Molecular plant-microbe interactions, 2023)
Grapevine fanleaf virus (GFLV) (genus Nepovirus, family Secoviridae) causes fanleaf degeneration, one of the most damaging viral diseases of grapevines. Despite substantial advances at deciphering GFLV-host interactions, how this virus overcomes the host antiviral pathways of RNA silencing is poorly understood. In this study, we identified viral suppressors of RNA silencing (VSRs) encoded by GFLV, using fluorescence assays, and tested their capacity at modifying host gene expression in transgenic Nicotiana benthamiana expressing the enhanced green fluorescent protein gene (EGFP). Results revealed that GFLV RNA1-encoded protein 1A, for which a function had yet to be assigned, and protein 1BHel, a putative helicase, reverse systemic RNA silencing either individually or as a fused form (1ABHel) predicted as an intermediary product of RNA1 polyprotein proteolytic processing. The GFLV VSRs differentially altered the expression of plant host genes involved in RNA silencing, as shown by reverse transcription-quantitative PCR. In a co-infiltration assay with an EGFP hairpin construct, protein 1A upregulated NbDCL2, NbDCL4, and NbRDR6, and proteins 1BHel and 1A+1BHel upregulated NbDCL2, NbDCL4, NbAGO1, NbAGO2, and NbRDR6, while protein 1ABHel upregulated NbAGO1 and NbRDR6. In a reversal of systemic silencing assay, protein 1A upregulated NbDCL2 and NbAGO2 and protein 1ABHel upregulated NbDCL2, NbDCL4, and NbAGO1. This is the first report of VSRs encoded by a nepovirus RNA1 and of two VSRs that act either individually or as a predicted fused form to counteract the systemic antiviral host defense, suggesting that GFLV might devise a unique counterdefense strategy to interfere with various steps of the plant antiviral RNA silencing pathways during infection.